Resolution of Sonographic Appendicitis in Pediatrics: a Point of Care Ultrasound Case-Series - Eric Scheier; Benjamin Taragin (CINQUILL Medical Publishers Inc., 2024)
Studies of pediatric appendicitis treated conservatively show a considerable rate of recurrence. Point of care ultrasound (POCUS) imaging at our facility is routinely performed for abdominal pain and may be more likely than radiology-performed ultrasound to encounter cases that then self-resolve. We present a case series collected from a POCUS quality assurance review from 2019 through 2022. Five children were identified with sonographic appendicitis on review of stored POCUS images, and subsequent improvement of pain. A pediatric radiologist reviewed blinded images and agreed with the POCUS interpretation in all five cases. No child in this series received antibiotics. The national patient database was used to ensure that the patients in this series did not present elsewhere with appendicitis. We suggest that these cases represent early appendicitis that self-resolved. Patients should be aware that POCUS showed signs of appendicitis, and should seek medical attention for recurrence of symptoms.